Effect of vitamin D supplementation - Biłogras, Jan; Karamus, Kornelia; Rejmak, Rafał; Borowska-Łygan, Martyna; Tomaszewski, Jakub; Strużek, Konrad; Urban, Wojciech (Journal of Education, Health and Sport, 2024)
Introduction Vitamin D is one of the most important vitamins in affecting the human body. It turns out that its influence is not limited to its health-promoting effect on the skeletal system, but may also play an important role in the immune system. In our study, we focused precisely on this aspect of vitamin D's action. Review method We used materials from PubMed for this purpose. We focused on articles and research papers published between 2019 and 2024. We reviewed the publications in terms of vitamin D supplementation and its effects on immunity, disease processes, patient recovery, COVID-19 patients, and some autoimmune diseases. Results Some studies show that vitamin D supplementation significantly improves immune function. It also improves prognosis and reduces mortality in COVID-19. The number of complications and severity of the course also decreases. Vitamin D supplementation also has a positive effect on the course of autoimmune diseases, allowing a reduction in the incidence and improving the outcome of some of them. Unfortunately, not all studies prove such beneficial effects of vitamin D. What is important, however, is that vitamin D may have a beneficial effect on the course of diseases, and the low cost of its use and high availability may prove to be the key to medical development. Conclusions Based on the accumulated studies, it can be concluded that vitamin D contributes to the improvement of immune system function. Some studies prove the beneficial effect of vitamin D supplementation on the course of some autoimmune diseases. The potential benefits of vitamin D supplementation, as well as its low cost, should be a key argument for further research and knowledge on this topic.